Recurrence of simple bone cyst: a case report and brief review of literature - Lucena, Ieda Milani de; Santos, Ingrid da Silva; Gamba, Thiago de Oliveira; Flores, Isadora Luana; Rados, Pantelis Varvaki (Journal of Oral Diagnosis, 2020)
Background: Simple bone cyst (SBC) is an uncommon intraosseous lesion, often inciden- tally discovered on routine radiological examination. The etiology remains unclear, and a definite diagnosis is confirmed during surgical exploration. Recurrence rates have been controversial. Case Report: This article presents a case of a 13-year-old boy with SBC in the posterior left region of the mandible and a brief review of previously published cases of recurring SBC. The patient denied a history of trauma. Surgical exploration revealed an empty cystic cavity and the clinical diagnosis of the SBC was established. A follow-up radiographic examination two years later revealed significant regression of the lesion. However, the lesion recurred after 4 years. A new surgical approach was performed and the diagnosis of recurrence of SBC was again established. In addition to this case, a review of 12 cases of recurring SBC is presented here. Conclusion: Clinicians should ensure a long-term follow-up of these patients. The patient is in follow-up for 10 years after the first surgical intervention without signs of recurrence.